If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(9x + -7) = (9x + 8)(x + -3) Reorder the terms: x(-7 + 9x) = (9x + 8)(x + -3) (-7 * x + 9x * x) = (9x + 8)(x + -3) (-7x + 9x2) = (9x + 8)(x + -3) Reorder the terms: -7x + 9x2 = (8 + 9x)(x + -3) Reorder the terms: -7x + 9x2 = (8 + 9x)(-3 + x) Multiply (8 + 9x) * (-3 + x) -7x + 9x2 = (8(-3 + x) + 9x * (-3 + x)) -7x + 9x2 = ((-3 * 8 + x * 8) + 9x * (-3 + x)) -7x + 9x2 = ((-24 + 8x) + 9x * (-3 + x)) -7x + 9x2 = (-24 + 8x + (-3 * 9x + x * 9x)) -7x + 9x2 = (-24 + 8x + (-27x + 9x2)) Combine like terms: 8x + -27x = -19x -7x + 9x2 = (-24 + -19x + 9x2) Add '-9x2' to each side of the equation. -7x + 9x2 + -9x2 = -24 + -19x + 9x2 + -9x2 Combine like terms: 9x2 + -9x2 = 0 -7x + 0 = -24 + -19x + 9x2 + -9x2 -7x = -24 + -19x + 9x2 + -9x2 Combine like terms: 9x2 + -9x2 = 0 -7x = -24 + -19x + 0 -7x = -24 + -19x Solving -7x = -24 + -19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19x' to each side of the equation. -7x + 19x = -24 + -19x + 19x Combine like terms: -7x + 19x = 12x 12x = -24 + -19x + 19x Combine like terms: -19x + 19x = 0 12x = -24 + 0 12x = -24 Divide each side by '12'. x = -2 Simplifying x = -2
| 4x+8x+11y+2w+3x-2y= | | k(k)=y | | 5x=4+-.1y | | 0=56+7x | | 0.16(18x+30)-8x= | | 4x-7w= | | 13s-234=3s-14 | | 10a-2b=-26 | | 2(9+x)=-15(4+x) | | -6=h/18 | | (7x-6)=6-7x | | 5x+17=5x+98 | | X^3-48=4x | | 30+8n=4(2n+7) | | x=2x-73 | | m+1.89=6.519 | | 7(x+4)=3(x+2) | | -6(1+7k)-5=-4K+27 | | -3t+6=60 | | 9p+5=-12 | | 3-5*4= | | -(6x+8)=-8-6x | | 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 | | 0.3(x+20)-0.05(x-10)=21.5 | | g(x)=17x^9+1 | | y=5x+150 | | (17x-7)+20x+15x+(12x-17)=360 | | 24+4b=6(b+2) | | u=4(2n+33)+5(n+1) | | 2(3z+1)-(2-6)= |